Peran Motivasi Pendidik dan Tenaga Kependidikan dalam Capaian Mutu Pendidikan di Sekolah Dasar - Muji Rahayu; Azizah Ramadhanti; Dinda Ruszayanthi; Prof. Dr. Azainil, M.Si.; Prof. Dr. Laili Komariyah, M.Si (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Excellent quality education is an important foundation in efforts to strengthen the competitiveness of a society. One of the elements that is very important in achieving this is the quality of educators and support staff in educational institutions. A study has been conducted to examine this aspect in depth, focusing on the situation at State Elementary School 001 Waru, Penajam Paser Utara Regency. The method used is a qualitative approach through literature analysis. Overall, the quality of educators and support staff at State Elementary School 001 Waru, Penajam Paser Utara Regency can be said to be satisfactory. However, there are still challenges that need to be overcome. Therefore, it is important for them to continue to participate in training and development programs organized by related parties. To face this challenge, close cooperation is needed between schools and related agencies, as well as a strong commitment from educators and support staff to continue learning and improving themselves. Such training and development will not only improve technical skills, but also their understanding of educational developments and community needs. With an awareness of the importance of improving the quality of education, State Elementary School 001 Waru, Penajam Paser Utara Regency can continue to advance in providing quality educational services for students. This not only benefits the individuals involved but also contributes to the development of a competitive society at the local and national levels. Therefore, concrete steps need to be taken to ensure that the quality of education at State Elementary School 001 Waru, Penajam Paser Utara Regency continues to improve in line with the times and global demands.